Mapping of Bandung Cultural Heritage Through The Historic Urban Landscape (HUL) Approach - Izzati, Husna; Adishakti, Laretna Trisnantari (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
Bandung is the capital city of West Java Province and is also included in Cekungan Bandung Area. The term Cekungan Bandung refers to its geomorphological condition in the form of a basin surrounded by hills and mountains. Bandung which is located in the highlands, has attracted the Dutch Colonials to develop plantations (e.g. quinine, coffee, tea) and also as a resort town. The progress of the colonial economy has brought Bandung city to become a famous tourist destination in the Dutch East Indies (i.e. Indonesia), with its rapidly growing European culture and architecture, making Bandung known as Europa in de Tropen. In the early 20th century Bandung city was planned as the replacement Capital of Batavia, with the construction of central government buildings along with the European settlements which were thick with a mixture of tropical architecture and European architecture styles which are still commonly found in this city. This study uses the Historic Urban Landscape (HUL) method which consists of seven stages, the process of identifying and mapping the layers of the heritage landscape of Bandung is the initial stage of HUL. The aim of this research is to obtain a complete perspective of natural, cultural, and human resources as the elements that form the Bandung Cultural Heritage, which can be used to study the next stages of HUL.